Defending Intrinsic Biological Essentialism. Issue 1 (January 2021) - Devitt, Michael
Abstract : In "Resurrecting Biological Essentialism, " I went against the consensus in the philosophy of biology by arguing that a Linnaean taxon, including a species, has an essence that is, at least partly, an underlying intrinsic, mostly genetic, property: this intrinsic nature explains both the truth of generalizations about the phenotypic properties of the taxon and why being in the taxon is explanatory. The current article is a response to two criticisms: that this intrinsic essentialism is at odds with certain biological variations and that this talk of intrinsic essences is an uncalled for metaphysical addition to biology.